With a rebel yell: Video gamers' responses to mass shooting moral panics. (March 2021) - Kneer, Julia; Ward, Michael R
When a moral panic happens, society believes that a group of people and/or their behaviour is responsible for a threat to society – without any evidentiary basis. How does the target group respond? In the video game context, gamers may fear that their pastime will be blamed for mass shootings leading to social stigma. Group members so threatened are hypothesized to react to protect their group identity. This leads to increased engagement in the activity under threat. In contrast, disasters that do not threaten the group would not affect the amount of video game play. We test these hypotheses by relating the amount of game play to incidents of mass shootings and non-shooting disasters for a large sample of individuals ( N  = 170, 000). Incidents of mass shootings that threaten the gamer community lead to increases in game playing while incidents of other disasters unrelated to gaming divert time away from gaming.